PERAN KOLABORASI DARING DALAM MENINGKATKAN KETERAMPILAN SOSIAL DAN KETERLIBATAN SISWA DI SEKOLAH DASAR: STUDI BIBLIOMETRIK - Nurlaila Nurlaila; Abas Oya; Nurlailatun Ramdani; Nurwalidainismawati Nurwalidainismawati (Pendikdas: Pendidikan Dasar, 2024)
This study aims to analyze the role of online collaboration in enhancing social skills and student engagement in elementary schools from 2019 to 2024. Using a bibliometric approach, data were collected from Crossref through the Publish or Perish application, focusing on keywords such as "online collaboration," "social skills," and "student engagement." A total of 810 publications were analyzed, indicating a positive trend in research on online collaboration, with a peak in publications occurring in 2022 with 253 articles, and the lowest number recorded in 2019 with 93 articles. The results show that online collaboration improves communication and cooperation skills among students and encourages their engagement in learning. Online collaboration tools, such as Google Classroom and Microsoft Teams, have enhanced student motivation and responsibility for their learning outcomes. However, challenges such as the digital divide and the need for teacher training have also been identified as barriers to implementing this method. This research provides important insights for educational practitioners and policymakers to optimize the use of technology in elementary education. With recommendations for further research on new technologies in online collaboration, this study emphasizes the significance of online collaboration as a key element in creating an inclusive and effective learning environment.